Addressing the Social and Political Embeddedness of Corruption - Mayo, Joshua Andrew Jay (Université d'Ottawa | University of Ottawa, 2016)
Despite significant progress in the research of corruption over the past few decades, the current scheme of anti-corruption strategies has failed to influence the hold of corruption across numerous countries. In attempting to understand why current policy responses to corruption have been generally ineffective, I ask the following question: do policy responses to corruption take social and political embeddedness into account, and are those policy responses adequate or inadequate as anti-corruption remedies as a result? I hypothesize that most anti-corruption programs either ignore or do not adequately take embeddedness into account. In order to answer this question, I introduce the socialization gap in traditional corruption literature, and fill this gap by situating a theory of social and political embeddedness of corruption within alternative texts. Using this theory, I test my hypothesis against a case study of six different World Bank anti-corruption programs. I find that five of the six programs could not adequately address the social embeddedness of corruption, though some efforts were made to address political embeddedness. The one successful program maintained an ideal balance between social and political reform.